PENGARUH MODEL PEMBELAJARAN NUMBERED HEAD TOGETHER (NHT) BERBASIS 4C TERHADAP HASIL BELAJAR MATEMATIKA KELAS IV SD PADA MATERI PECAHAN - Santoso, Sanny Setianing; Kharisma Eka Putri; Frans Aditia Wiguna (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2024)
This research was based on the results of researchers' observations at one of the schools in Nganjuk Regency. From the results of these observations, it is known that students' mathematics learning outcomes are low, and there are still many who have not completed the KKM, especially in 2021/2022. Teachers still dominate the classroom and do not involve students in the learning process. The learning model that teachers often use in learning activities does not involve students in the learning process so that there is no interaction between teachers and students in the classroom causing the atmosphere in the classroom to be passive. The aim of this research is to determine the influence of the 4C-based Numbered Head Together (NHT) learning model, the influence of the conventional model, and the difference in the influence of the 4C-based Numbered Head Together (NHT) learning model and the conventional model on class IV mathematics learning outcomes on fractions at SDN 1 Singkalanyar. The population in this study focused on class IV students at SDN 1 Singkalanyar, totaling 36 students. This research uses quantitative research techniques with experimental design methods. The experimental design used was a Pretest Posttest Control Group Design in the control group before and after the trial. The variables in this research use the 4C-based Numbered Head Together (NHT) learning model to determine mathematics learning outcomes in fraction material. The conclusions of the research results are (1) The 4C-based Numbered Head Together (NHT) learning model has an influence on mathematics learning outcomes for grade IV elementary school on fraction material at SDN 1 Singkalanyar. This is proven by the tcount value of 8,831 ≥ ttable 1,740 at the 5% significance level. (2) The conventional learning model influences the mathematics learning outcomes of grade IV elementary school on fractions at SDN 1 Singkalanyar. This is proven by the tcount value of 2,814 ≥ ttable 1,740 at the 5% significance level. (3) There is a difference in the effect of using the 4C-based Numbered Head Together (NHT) learning model compared to not using the 4C-based Numbered Head Together (NHT) learning model on mathematics learning outcomes for class IV elementary school on fraction material at SDN 1 Singkalanyar. This is proven by the value of tcount 2,034 ≥ ttable 1,691 at a significance level of 5%. Thus, overall it can be concluded that the Numbered Head Together (NHT) learning model based on 4C has an influence on the mathematics learning outcomes of class IV elementary school on fraction material at SDN 1 Singkalanya.